GAMBARAN TINGKAT KEBUGARAN JASMANI MAHASISWA LAKI-LAKI FAKULTAS TEKNIK UNIVERSITAS DIPONEGORO - Weildsrie Ewildsycraev R.; Ari Udiyono; Lintang Dian Saraswati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Physical fitness is an important component that students need to follow the lecture. Similarly, the students of Faculty of Engineering, an engineering student requires optimal fitness in particular through the activities of lectures are more dense than the other faculties. Research in the School of Public Health Diponegoro University in 2013 found the 67.9% of the students had less fitness level (poor). The purpose of this study is to describe the factors associated with the level of physical fitness of male students of Faculty of Engineering, University of Diponegoro. This research is a descriptive study with cross sectional design. This research subject is a male student of the Faculty of Engineering of Diponegoro University who actively enrolled a total of 100 people. The sampling technique is simple random sampling. From the results of the study concluded that 72% of respondents had a physical fitness less category, 82% of respondents had a physical activity light weight category. Suggestions for students of the Faculty of Engineering is to do exercise at least 1 time a week. Suggestions for Undip engineering faculty will not provide practicum on holiday.